Business process management cases digital innovation and business transformation in practice - Mendling, Jan; vom Brocke, Jan (Management for Professionals, 2018)
This book is the first to present a rich selection of over 30 real-world cases of how leading organizations conduct Business Process Management (BPM). The cases stem from a diverse set of industry sectors and countries on different continents, reporting on best practices and lessons learned. The book showcases how BPM can contribute to both exploitation and exploration in a digital world. All cases are presented using a uniform structure in order to provide valuable insights and essential guidance for students and practitioners.